Macrofauna accelerates nutrient cycling through litterfall in cocoa agroforestry systems - Oyedele, O.; Hougni, D.-G.J.M.; Hauser, S.; Schut, A.G.T.; Woittiez, L.S.; Rusinamhodzi, L.; Ogunlade, M.O.; Giller, K.E. (2025)
This study aimed to better understand nitrogen (N), phosphorus (P), and potassium (K) cycling through litterfall in smallholder cocoa agroforestry systems and to assess if these nutrient flows can be measured using standard litterbags. Annual litter production, relative mass loss, and nutrient loss rates from cocoa leaf litter were evaluated in three farms in south-western Nigeria with and without macrofauna access. Litterfall was measured fortnightly close to the base of the cocoa tree and at the edge of the tree canopies from January 2020 to December 2021. Leaf litter decomposition rates were determined over 388 days in 2 mm mesh litterbags to exclude macrofauna and in frames open to the soil surface to allow macrofauna access. Concentrations of C, N, P, and K were measured in the remaining litter at 180, 244, 314, and 388 days after incubation. Annual estimates of litterfall (10.62 Mg DM ha−1) did not significantly differ between the traps close to and away from the cocoa tree trunk. Nutrient cycling from litter was estimated at approximately 101 kg N, 5 kg P, and 89 kg K ha−1 year−1. Relative litter decomposition rates (k) significantly differed between frames and litterbags. Macrofauna access significantly reduced the C:N ratio in the remaining litter and increased N and P loss from the litter layer by 28 and 69%, respectively. In conclusion, nutrient flows through litterfall are considerable, and N and P transfer rates to soil are likely underestimated in litterbag experiments that exclude macrofauna.